The studies of structural stability of LiNi0.5Mn1.5O4 spinel - Park, Sung-Bin; Kim, Yool-Koo; Lee, Wan-Gyu; Cho, Won-Il; Jang, Ho (KOREAN INST METALS MATERIALS, 2008)
The present paper focuses on the structural stability of LiNi0.5Mn1.5O4 during lithiation/delithiation of Li ions and compared to that of LiMn2O4 LiMn2O4 and LiNi0.5Mn1.5O4 powders are synthesized using a sol-gel method and their structural and electrochemical properties are investigated by XRD, SEM, and charge-discharge tests. LixMn2O4 and LixNi0.5Mn1.5O4(X = 0.9,0.5,0.1) specimens are obtained after charge/discharge tests by controlling the cut-off voltage for XRD and TEM investigation. The charge-discharge tests shows that initial capacity of LiNi0.5Mn1.5O4 is 125 mAh/g and that of LiMn2O4 is around 100 mAh/g. The capacity of LiNi0.5Mn1.5O4 is maintained 95% of its initial capacity whereas the capacity of LiMn2O4 is maintained 65% of its initial capacity.
Keywords: LITHIUM-ION BATTERIES; INTERCALATION CATHODES; LIMN2O4; SYSTEM; PHASE